Students’ Perception on the Classroom-Task-Based Subject Delivery Of The Subject Of Evaluation Of The Fine Art Learning - Hasnawati, Hasnawati; Alimuddin, Alimuddin (Universitas Negeri Makassar, 2014)
The study was objective to describe students’ sight on the subject delivery through the classroom-task-based on the subject of fine art learning evaluation. The subject of the study was all students of the Fine Art Program about 45 students. The study was utilized descriptive qualitative method. The required data was collected by means of questionary, interview, and documentation schemes. Data has gathered to be utilizing questionary, observations sheet, interview sheet, and camera. The data was analyzed qualitatively descriptive scheme. Result of the study was suggested that classroom-task-based subject delivery may applied in good manner for the subject of fine art learning, that is could be support students to decrease their problem in acquiring learning contents, to support student’s performance to finish all questions of the related subject, students is to be enjoyful, that is promotes their motivation and active in their class, students quickly comprehends delivered subject, students’ is to be facilitated in finishing their assigned tasks.